Prehistoric maritime structures in Dalmatia and Kvarner - Parica, Mate (Morepress Books, 2024)
Reconstruction of prehistoric events poses many challenges to researchers. There is a wide time frame where our knowledge is very scarce, while each new research brings new elements that can complete previous conclusions. On the one hand, the lack of written sources deprives us of valuable information about the processes within certain space and time, while, on the other hand, the same shortcoming deprives us of the existence of a control mechanism in making conclusions. As a consequence, there are long-established hypotheses that have never been proven, and we accept them today as absolute scientific facts. The impetus for this work came from participating in research of the submerged Bronze Age settlement of Ričul, some twenty kilometres south-east of Zadar, when the idea was born that it might be possible to determine a model for identifying strategic places where similar sites could be located. The mentioned approach surpassed our expectations, considering that twenty, hitherto unknown, prehistoric submerged sites were discovered in a relatively short time. The newly discovered sites are very important for learning about the techniques of building maritime structures. However, even more important is the possibility of reconstructing social, economic and military and political relations among the inhabitants of the Adriatic in prehistory, especially in the Bronze and Iron Age. After the first few successful underwater reconnaissances, the model proved functional, and the very fact that it is possible to find entirely new prehistoric sites by examining strategically important points, provided favourable geomorphological predispositions, of course, also had this research as a result.